Investigation of plant growth regulation activity of ([1,2,4]triazolo[1,5-c] quinazolin-2-ylsulfanyl)carboxylic acids and amides on Cucumis sativus L. Roots - Antypenko, L. M.; Kovalenko, S. I.; Kornet, M. M.; Brazhko, O. O.; Антипенко, Людмила Миколаївна; Коваленко, Сергій Іванович (Zaporoshye State Medical University, 2012)
Роботу присвячено розширенню ряду відомих регуляторів росту рослин серед похідних триазолу, зокрема ([1,2,4]триазоло[1,5-с]хіназоліну-2-ілсульфаніл)карбонових кислот та амідів. Біологічну активність останніх досліджено in vitro на коренях Cucumis sativus L. Кращими стимуляторами росту виявились кислоти 3 (0,02 мг/мл) і 4 (0,5 мг/мл), перевищивши активність гібереніну. Работа посвящена расширению известных регуляторов роста растений среди производных триазола, а именно ([1,2,4]триазоло[1,5-с]хиназолин-2-илсульфанил) карбоновых кислот и амидов. Биологическая активность последних исследована in vitro на корнях Cucumis sativus L. Лучшими стимуляторами роста оказались кислоты 3 (0,02 мг/мл) и 4 (0,5 мг/мл), превысив активность гиберенина. The present work is dedicated to the enlargement of the known plant growth regulators among triazole derivatives, namely, ([1,2,4]triazolo[1,5-c]quinazolin-2-ylsulfanyl) carboxylic acids and amides. The biological activity ща the latter’s was investigated in vitro via direct organogenesis of Cucumis sativus L. roots. The best growth stimulators appeared to be acid 3 (0.02 mg/mL) and acid 4 (0.5 mg/mL), exceeding the activity of gibberellines.
Keywords: рострегулирующая активность; 2-тио-[1,2,4]триазоло[1,5-c]; Хиназолины; Cucumis sativus L.; growth regulation activity